Data and R-scripts from: Multiple stressors: negative effects of nest predation on the viability of a threatened gull in different environmental conditions ... - Bårdsen, Bård-Jørgen; Bustnes, Jan Ove (Dryad, 2022)
Here, we provide the data and R-scripts used in: Bård-Jørgen Bårdsen and Jan Ove Bustnes (2022). Multiple stressors: negative effects of nest predation on the viability of a threatened gull in different environmental conditions. Journal of Avian Biology. https://doi.org/10.1111/jav.02953. Bård-Jørgen Bårdsen and Jan Ove Bustnes (2023). Correction to Multiple stressors: negative effects of nest predation on the viability of a threatened gull in different environmental conditions. Journal of Avian Biology. https://doi.org/10.1111/jav.12915. This study assessed the viability of a population of the lesser black-backed gull (Larus fuscus fuscus) using data collected from 2005-2020 from a nature reserve in Northern Norway. The study merged results from statistical analyses of empirical data with a Leslie model. Here, we provide the underlying data and the R-scripts used to analyse the data and run the model. The data set includes information about reproduction at several stages (laying, hatching and fledgling), ... : Bårdsen and Bustnes (2022), including the online Supplementary Material (Appendix S1-2), provide a detailed description of the study area and the empirical data. In the downloadable software ('ToBePublished.zip'), we provide data, metadata, and R-scripts for the statistical analyses and the models. Please confer with the 'README.txt' in 'ToBePublished.zip' for more information. We also include the data (without the scripts) from our study area as a downloadable dataset ('Data.zip'; see the included 'README.txt' for details). ...